2021
DOI: 10.1063/5.0060481
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning framework for quantum sampling of highly constrained, continuous optimization problems

Abstract: In the recent years, there is a growing interest in using quantum computers for solving combinatorial optimization problems. In this work, we developed a generic, machine learningbased framework for mapping continuous-space inverse design problems into surrogate quadratic unconstrained binary optimization (QUBO) problems by employing a binary variational autoencoder and a factorization machine. The factorization machine is trained as a low-dimensional, binary surrogate model for the continuous design space and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Previously, it has been demonstrated that autoencoder-assisted inverse design frameworks can be efficiently applied to multi-objective optimization problems. These approaches could be used for global optimization via hybridization with different heuristics algorithms, , including frameworks that allow sampling globally optimized solutions by leveraging classical and quantum quadratic unconstrained binary optimization solvers . The developed VAE-TO framework opens the way to realize the multi-objective optimization of the lightsail design employing the previously proven concept of physics-driven compressed space engineering …”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been demonstrated that autoencoder-assisted inverse design frameworks can be efficiently applied to multi-objective optimization problems. These approaches could be used for global optimization via hybridization with different heuristics algorithms, , including frameworks that allow sampling globally optimized solutions by leveraging classical and quantum quadratic unconstrained binary optimization solvers . The developed VAE-TO framework opens the way to realize the multi-objective optimization of the lightsail design employing the previously proven concept of physics-driven compressed space engineering …”
Section: Discussionmentioning
confidence: 99%
“…What makes a QA attractive is the theoretical guarantee of finding the global optimal solution under the assumption of ideal qubits and slow annealing . Although this goal is not attainable currently, recent successful case studies in materials science , imply that the quality of qubits has improved to the point that they are practically useful. In addition, QA-based methods are likely to benefit from future development of quantum technologies.…”
mentioning
confidence: 99%
“…A necessity for solving low-rank Ising problems arises when we consider the learning of combinatorial optimization problems [41][42][43]. For example, in a study on the automated design of metamaterials [41], the authors train a factorization machine [44], which has a low-rank quadratic form similar to the SPBM Hamiltonian, and find low-energy candidates for metamaterials using a D-Wave quantum annealer.…”
mentioning
confidence: 99%